Pembuatan Marketplace Sebagai Media Promosi Online Lembaga Kursus Dan Pelatihan Provinsi Jawa Timur - Moch Husein; Nia Saurina; Firman Hadi S Pratama (Informatics Engineering Department-UWKS, 2017)
A large number of students is one sign that an institution and training courses it has successfully become a place that deserves to be trusted by the public. To obtain a large number of learners who require a great effort and to funds. In bringing participants the need for a promotion which can attract prospective students to participate in a training course and institution. Using Prototype method which has the steps of research, namely: Data Collection, Analysis and Design, Prototype Pembuatam I, Evaluation Prototype I, Manufacture Prototype II Prototype II Evaluation and Documentation The results of this study can register new CGC, CGC promotion, registration of learners to LKP destination, search CGC and CGC data reports and Learners.